2018
DOI: 10.1007/s00402-018-2894-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of glenoid labral tears using 3-tesla MRI vs. 3-tesla MRA: a systematic review and meta-analysis

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Another meta-analysis demonstrated that MRA was superior to MRI for the detection of SLAP lesions [19]. A recent meta-analysis from 2018, involving 10 studies, revealed that 3.0 T MRA improved sensitivity for the diagnosis of anterior and posterior labral tears, but reduced specificity in the diagnosis of SLAP tears [20].…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis demonstrated that MRA was superior to MRI for the detection of SLAP lesions [19]. A recent meta-analysis from 2018, involving 10 studies, revealed that 3.0 T MRA improved sensitivity for the diagnosis of anterior and posterior labral tears, but reduced specificity in the diagnosis of SLAP tears [20].…”
Section: Introductionmentioning
confidence: 99%
“…A diagnosis was made and supported high-quality 3-T MRI scans, which have been proven to provide good utility in diagnosing these injuries. 1 For each affected shoulder, the size and location of the tear were documented. Labral tears were classified in terms of the location as anterior, posterior, or combined anterior and posterior.…”
Section: Methodsmentioning
confidence: 99%
“…Where 3T imaging is available, the additional diagnostic yield of MRAs over conventional MRIs may be less pronounced. Conventional MRI at 3T has comparable accuracy to MRAs at 3T for rotator cuff tears, though MRAs have greater sensitivity for labral tears [16][17][18]. Magee [19] reported that the likelihood of finding an additional finding on MRA is small (6%) if an initial non-arthrographic conventional MRI was abnormal.…”
Section: Impact Of Increased Magnet Field Strength On Mrimentioning
confidence: 99%